2023
DOI: 10.1039/d3qi01715j
|View full text |Cite
|
Sign up to set email alerts
|

LiVTeO5: a mid-infrared nonlinear optical vanadium tellurate crystal exhibiting enhanced second harmonic generation activities and notable birefringence

Yuheng She,
Jinmiao Jiao,
Zheng Wang
et al.

Abstract: Mid-infrared (IR) nonlinear optical (NLO) crystals are of great interest for applications in laser science and technology. Nevertheless, the pursuit of mid-IR NLO crystals displaying exceptional comprehensive performance remains a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…11 Notably, germanate-based materials inherently possess potential for applications in both linear and nonlinear optics, due to their extensive visible and infrared transmittance range, as well as impressive thermal and chemical stability. 12–14 For instance, through the rational integration of customized functional motifs comprising antiparallel [GeO 4 ] tetrahedra and distorted [NbO 6 ] octahedra, the Cs 3 Nb 5 GeO 16 crystal not only demonstrates a wide transparent window but also achieves a breakthrough of experimental birefringence of 0.19 @532 nm among the available germanate oxides, signifying its significant potential for manipulating polarized light. 15 Recently, Ye et al have reported findings on a niobium germanate oxide, 16 K 3 Nb 3 Ge 2 O 13 , which showcases [GeO 4 ] units and distinctive [Nb 3 O 12 ] ∞ tubular chains constructed by circular [Nb 3 O 15 ] tripolymers.…”
Section: Introductionmentioning
confidence: 99%
“…11 Notably, germanate-based materials inherently possess potential for applications in both linear and nonlinear optics, due to their extensive visible and infrared transmittance range, as well as impressive thermal and chemical stability. 12–14 For instance, through the rational integration of customized functional motifs comprising antiparallel [GeO 4 ] tetrahedra and distorted [NbO 6 ] octahedra, the Cs 3 Nb 5 GeO 16 crystal not only demonstrates a wide transparent window but also achieves a breakthrough of experimental birefringence of 0.19 @532 nm among the available germanate oxides, signifying its significant potential for manipulating polarized light. 15 Recently, Ye et al have reported findings on a niobium germanate oxide, 16 K 3 Nb 3 Ge 2 O 13 , which showcases [GeO 4 ] units and distinctive [Nb 3 O 12 ] ∞ tubular chains constructed by circular [Nb 3 O 15 ] tripolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the second harmonic generation (SHG) effect of NLO crystals, it is easier to realize the solid-state and miniaturization of laser devices. Over the past few decades, the popularization of laser application in increasing scenarios has stimulated enthusiasm for the development of more novel NLO crystals. …”
Section: Introductionmentioning
confidence: 99%
“…58 Very recently, the potential nonlinear optical material, vanadium tellurate (LiVTeO 5 ), was created through the combination of Te 4+ cations and V 5+ cations. 59 While, until now, only NbTe 2 and TaTe 2 have been investigated as SAs in mode-locked fiber lasers and PQS solid-state lasers, respectively. Experimentally, Zhang et al 60 and Shang et al 61 investigated the nonlinear optical properties in a mode-locked fiber laser with NbTe 2 −PVA film SA as the mode-locked device and proved that NbTe 2 demonstrates as a broadband SA to produce mode-locked pulses within fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable conductivity, flexibility, and catalytic prowess of 2D 1T-VTe 2 have paved the way for its outstanding performance in various electrode-related applications. , Furthermore, electric fields can induce phase transitions, resulting in nonvolatile and controllable resistance states, which implies that 1T-VTe 2 thin films hold promise as innovative charge density wave materials for memory devices, enabling logic state switching via electric field manipulation. , The VTe 2 /MXene heterostructure demonstrated improved energy storage performance resulting from the synergistic interplay between the 3D network of VTe 2 and MXene . Very recently, the potential nonlinear optical material, vanadium tellurate (LiVTeO 5 ), was created through the combination of Te 4+ cations and V 5+ cations . While, until now, only NbTe 2 and TaTe 2 have been investigated as SAs in mode-locked fiber lasers and PQS solid-state lasers, respectively.…”
Section: Introductionmentioning
confidence: 99%